An Evaluation of Some Japanese Lisianthus (Eustoma grandiflorum) Varieties Grown in Bangladesh (The Agriculturists, 2013)
A pot experiment was conducted for the first time in Bangladesh, at the Horticulture Farm of Sher-e- Bangla Agricultural University, Dhaka during November, 2010 to July, 2011 to asses the adaptability of seven lisianthus (Eustoma grandiflorum) cultivars namely Micky Rose, Pink Rose, Azuma No Yosooi, Purple Edge Glass, Piccolo Blue, Mellow Purple and Royal Violet for commercial cultivation in Bangladesh. The experiment was conducted in a Randomized Complete Block Design with nine replications. Significant differences among cultivars were noted for all the attributes evaluated. The highest number of flowers (16.0/plant) was produced by Piccolo Blue and the lowest from Pink Rose (7.0/plant). All the cultivars in this study showed very good shelf life (12.0-25.0days) in normal condition. All the seven lisianthus cultivars performed satisfactorily as ideal cut flowers. Further work may be done to develop these as commercial cultivars in Bangladesh. DOI: http://dx.doi.org/10.3329/agric.v11i1.15243 The Agriculturists 2013; 11(1) 56-60